Assessment Of Drug Use And Provider Compliance In Outpatient Care - Rita Prameswari; Rina Kurniasri Kusumaratna; Erna Kristin (The Journal of Hospital Accreditation, 2024)
Background: Outpatient services represent a major source of hospital revenue and require efficient resource management. At AN-NISA Hospital, the neurology and psychiatry outpatient clinics showed the largest negative gap between INA-CBGs tariffs and hospital costs. Drug expenditures accounted for approximately 95% of the total INA-CBGs tariffs. Objective: To evaluate drug use indicators and provider compliance and to determine their association with drug use costs in neurology and psychiatry outpatient clinics. Methods: This observational analytic study employed a cross-sectional design with total sampling. A total of 769 prescriptions from National Health Insurance (JKN) outpatients with the two most common diagnoses and the highest drug use costs during October 2021 were analyzed. Drug use indicators were evaluated using WHO and National Formulary standards. Simple linear regression assessed the relationship between each independent variable and drug use costs, while multiple linear regression identified the strongest predictors. Results: Prescribing practices in both clinics did not meet WHO standards regarding adherence to the National Formulary, compliance with Referral Program (PRB) prescribing restrictions, the average number of drugs prescribed per prescription, and provider compliance. Generic prescribing met WHO standards only in the psychiatry clinic. Drug utilization costs in the psychiatry clinic were significantly associated with National Formulary prescribing (R=0.774), PRB prescribing (R=−0.092), generic prescribing (R=−0.611), the average number of drug items per prescription (R=0.221), and provider compliance (R=−0.478) (all p<0.05). In the neurology clinic, significant associations were found for National Formulary prescribing (R=0.682), PRB prescribing (R0.073), generic prescribing (R=−0.323), and provider compliance (R=−0.225), whereas the number of drug items prescribed showed no significant association (R=0.009; p>0.05). Generic prescribing was the strongest predictor of drug utilization costs in both neurology (β=−0.235) and psychiatry (β=−0.499). Conclusion: Drug use indicators and provider compliance in the neurology and psychiatry outpatient clinics have not fully met established standards and were significantly associated with drug use costs. Increasing generic prescribing may improve prescribing efficiency and reduce medication costs. Multidisciplinary collaboration among hospital management, pharmacists, information technology personnel, and clinicians is essential to promote rational prescribing and optimize healthcare costs.